Difference between revisions of "009A Sample Midterm 3, Problem 1"

From Math Wiki
Jump to navigation Jump to search
Line 102: Line 102:
 
\displaystyle{\lim _{x\rightarrow \infty} \frac{-2x^3-2x+3}{3x^3+3x^2-3}} & = & \displaystyle{\lim _{x\rightarrow \infty} \frac{(-2x^3-2x+3)}{(3x^3+3x^2-3)} \frac{(\frac{1}{x^3})}{(\frac{1}{x^3})}}\\
 
\displaystyle{\lim _{x\rightarrow \infty} \frac{-2x^3-2x+3}{3x^3+3x^2-3}} & = & \displaystyle{\lim _{x\rightarrow \infty} \frac{(-2x^3-2x+3)}{(3x^3+3x^2-3)} \frac{(\frac{1}{x^3})}{(\frac{1}{x^3})}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\lim_{x\rightarrow 0} \frac{-2-\frac{2}{x^2}+\frac{3}{x^3}}{3+\frac{3}{x}-\frac{3}{x^3}}}.
+
& = & \displaystyle{\lim_{x\rightarrow \infty} \frac{-2-\frac{2}{x^2}+\frac{3}{x^3}}{3+\frac{3}{x}-\frac{3}{x^3}}}.
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
Line 115: Line 115:
 
\displaystyle{\lim _{x\rightarrow \infty} \frac{-2x^3-2x+3}{3x^3+3x^2-3}} & = & \displaystyle{\lim_{x\rightarrow \infty} \frac{-2-\frac{2}{x^2}+\frac{3}{x^3}}{3+\frac{3}{x}-\frac{3}{x^3}}}\\
 
\displaystyle{\lim _{x\rightarrow \infty} \frac{-2x^3-2x+3}{3x^3+3x^2-3}} & = & \displaystyle{\lim_{x\rightarrow \infty} \frac{-2-\frac{2}{x^2}+\frac{3}{x^3}}{3+\frac{3}{x}-\frac{3}{x^3}}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\lim_{x\rightarrow \infty} (-2-\frac{2}{x^2}+\frac{3}{x^3})}{\lim_{x\rightarrow \infty} (3+\frac{3}{x}-\frac{3}{x^3})}}\\
+
& = & \displaystyle{\frac{\displaystyle{\lim_{x\rightarrow \infty} \bigg(-2-\frac{2}{x^2}+\frac{3}{x^3}\bigg)}}{\displaystyle{\lim_{x\rightarrow \infty} \bigg(3+\frac{3}{x}-\frac{3}{x^3}\bigg)}}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\lim_{x\rightarrow \infty} -2 +\lim_{x\rightarrow \infty} \frac{2}{x^2} +\lim_{x\rightarrow \infty} \frac{3}{x^3}}{\lim_{x\rightarrow \infty} 3+\lim_{x\rightarrow \infty} \frac{3}{x}-\lim_{x\rightarrow \infty}\frac{3}{x^3}}} \\
+
& = & \displaystyle{\frac{\displaystyle{\lim_{x\rightarrow \infty} -2 +\lim_{x\rightarrow \infty} \frac{2}{x^2} +\lim_{x\rightarrow \infty} \frac{3}{x^3}}}{\displaystyle{\lim_{x\rightarrow \infty} 3+\lim_{x\rightarrow \infty} \frac{3}{x}-\lim_{x\rightarrow \infty}\frac{3}{x^3}}}} \\
 
&&\\
 
&&\\
 
& = & \displaystyle{\frac{-2+0+0}{3+0+0}}\\
 
& = & \displaystyle{\frac{-2+0+0}{3+0+0}}\\

Revision as of 18:41, 13 April 2017

Find the following limits:

(a) If    find  

(b) Find  

(c) Evaluate  


Foundations:  
1. If    we have
       
2. Recall
       


Solution:

(a)

Step 1:  
First, we have
       
Therefore,
       
Step 2:  
Since    we have

       

Multiplying both sides by    we get
       

(b)

Step 1:  
First, we write
       
Step 2:  
Now, we have

       

(c)

Step 1:  
First, we have
       
Step 2:  
Now, we use the properties of limits to get

       


Final Answer:  
    (a)    
    (b)    
    (c)    

Return to Sample Exam